Kant und die Überwindung der phsikotheologischen Betrachtung der geographisch-kosmologischen Fakten - Büttner, Manfred (ERDKUNDE, 1975)
The following points are dealt with: 1 Why the physico-theological interpretation of geographic cosmological reality came about in the 18th century and what consequences there were for geography. 2 Why Kant was able to overcome this interpretation and substitute causal mechanism, thereby giving geography its decisive future form so that it is possible to speak today to 2 great epochs in the history of geography, the time before Kant and the time after. to 1: The physico-theological interpretation should be seen as a theological reaction (and practically all geographers at that time were theologicans) to the questioning, brought about by the Age of Enlightenment, of the divine world order. With the help of geographical facts attempts were made to overcome the tensions between theology and science, particularly geography, by stressing teleological command of the causal mechanism (Wolff), in that a theological goal namely the revelation of divine providence was attributed to geography. to 2: Kant showed that geography is theologically neutral; it is not possible, within the limits of human reason, to infer transcendence from immanence, that is to use geography as evidence for the divine world order.